Thioamide construction via sulfur interrupted Brook rearrangement - Shunmin Zhang; Yanyan Liao; Xuefeng Jiang (Green Synthesis and Catalysis, 2025)
Thioamide was straightforwardly constructed via a chemoselective one-pot synthesis, employing acylsilanes in conjunction with diverse amines and elemental sulfur. The driving force of thioamidation stemmed from silane migration, a synergy process of lone pair electron attack from amine and more stable Si–O bond formation, followed by the nucleophilic activation of elemental sulfur via carbanion intermediate. The leaving trend of trimethylsilanolate and nucleophilicity of linear polysulfur facilitated the cleavage of the S–S bond affording thioamide. A variety of sensitive functional groups, including unprotected hydroxyl, carboxyl and difluoride substitution moieties, are well tolerated under the reaction conditions. Site-selective introduction of thioamide was further demonstrated for the biologically active molecule linkage, displaying the advantages compared with the conventional Lawesson's reagent.